HEALTH WORKER SUPPORT TO IMPROVE SELF-MANAGEMENT OF HYPERTENSION PATIENTS: A CROSS-SECTIONAL STUDY - Tata Mahyuvi; Siti Mar'atul Munawaroh (Nursing Sciences Journal, 2026)
Background: Poor self-management, characterized by medication non-adherence and unhealthy lifestyles, significantly contributes to uncontrolled hypertension. Low self-efficacy in managing blood pressure remains a critical challenge in community health. Objective: This study evaluated the correlation between Health Worker Support and self-management practices among hypertensive patients. Methods: A quantitative cross-sectional study was conducted in December 2023 with 112 respondents selected via purposive sampling. Inclusion criteria included patients aged 19–65, diagnosed with uncomplicated hypertension, possessing a Glasgow Coma Scale (GCS) of 15 (E4V5M6), and being literate. Data were collected using healthcare support and self-management questionnaires, then analyzed using the Spearman Rank correlation test (alpha < 0.05).Results: Statistical analysis revealed a significant positive correlation between healthcare provider support and patient self-management (p= 0.003).Conclusion: Professional Health worker support is pivotal in enhancing self-management among hypertensive individuals. To optimize patient quality of life and prevent complications, healthcare providers should intensify proactive monitoring and educational interventions to foster better self-care autonomy.